(untitled) (Zien Journal of Social Sciences and Humanities, 2024)
Uzbek in the language to the hand wearable jewelry decoration items two , ie wrist and to the finger wearable decoration from items consists of In our language this jewelry of items from the face more than types there is . This is jewelry decoration items ( ie ring , bracelet and others ) of appear to be long to history go is worn